Noah is solving the inequality 7x + 5 > 2x + 35. First, he solves the equation 7x + 5 = 2x + 35 and gets x = 6.

How does the solution to the equation 7x + 5 = 2x + 35 help Noah solve the inequality 7x + 5 > 2x + 35? Explain your reasoning.

Respuesta :

Answer:

Step-by-step explanation:

7x+5>2x+35

5x>30

x>6

Inequalities are used to relate unequal expressions.

The solution to the inequality is: [tex]\mathbf{x > 6}[/tex]

The inequality is given as:

[tex]\mathbf{7x + 5 > 2x + 35}[/tex]

When Noah solved the inequality, he expressed the inequality sign ( > ) as =

So, we have:

[tex]\mathbf{7x + 5 = 2x + 35}[/tex]

The solution is:

[tex]\mathbf{x = 6}[/tex]

Notice that the sign in the original expression is >

So, Noah needs to convert the = sign back to the original sign of the inequality i.e. >

Hence, the solution to the inequality is:

[tex]\mathbf{x > 6}[/tex]

Read more about inequalities at:

https://brainly.com/question/11612965